Chlorophyll fluorescence in the evaluation of photosynthetic electron transport chain inhibitors in the pea - Farias, Marcio; Martinazzo, Emanuela; Bacarin, Marcos (Revista Ciência Agronômica, 2015)
The study aimed to evaluate the behavior of the chair of photosynthetic electron transport in the presence of DCMU and atrazine in detached leaves of pea through simultaneous measurements of the kinetics of fluorescence transient, fluorescence delayed and modulated reflection at 820 nm. The petioles of the leaves were immersed for two hours in solution of inhibitors at concentrations of 0 (control), 25, 50, 100, 250 and 500 mM. Measurements of the kinetics of fluorescence transient and fluorescence delayed and modulated reflection at 820 nm were recorded simultaneously by the M-PEA fluorometer. Simultaneous measurement of fluorescence transient, fluorescence delayed and modulated 820 nm reflection is important for assessments of the photosynthetic electron transport chain activity tool. The use of specific inhibitors of the electron transport chain allows you to collect and correlate a lot of information about the effect of different inhibitors at specific points in the photosynthetic electron transport chain. DCMU and atrazine are inhibitors of photosystem II and the concentration of 500 mM affects more strongly the flow of photosynthetic electrons.